The influence of leukocytospermia on the outcomes of assisted reproductive technology - Cavagna, Mario (2012)
Background: It is not well established whether the increased number of leukocytes in the seminal fluid impairs the outcomes of assisted reproductive technology (ART). This investigation analysed the outcomes of the intracytoplasmic sperm injection (ICSI) and intracytoplasmic morphologically selected sperm injection (IMSI) cycles in couples in which the male partner exhibited leukocytospermia.Methods: A total of 100 cycles in 100 couples were included in this study. For the ICSI or IMSI procedures, the patients were divided into two groups according to the presence or absence of leukocytospermia and then matched by (female) age:- ICSI: Group I (n = 25): Leukocytospermia - semen samples with a leukocyte count of greater than or equal to 1 x 10(6)/mL; and Group II (n = 25): Non-leukocytospermia - semen samples with a leukocyte count < 1 x 10(6)/mL.- IMSI: Group I (n = 25): Leukocytospermia; and Group II (n = 25): Non-leukocytospermia.The endpoints included the rates of fertilisation, implantation, clinical pregnancy, miscarriage, ongoing pregnancy and live birth. Student's t-tests, Mann-Whitney tests and Chi-square tests were performed, and P < 0.05 was considered significant.Results: The data from the ICSI groups showed that leukocytospermia did not have a negative influence on the rates of fertilisation (Group I: 57.9+/-30.2%, Group II: 61.9+/-27.7%; P = 0.74), implantation (Group I: 12.3%; Group II: 13.5%; P = 0.93), clinical pregnancy (Group I: 24%; Group II: 24%; P = 1.0), miscarriage ( Group I: 0, Group II: 0), ongoing pregnancy (Group I: 24%; Group II: 24%; P = 1.0), or live births (Group I: 24%; Group II: 24%; P = 1.0). Similarly, the data from the IMSI groups also showed that the leukocytospermia did not have a negative influence on the rates of fertilisation (Group I: 67.6+/-24.6%, Group II: 59.5+/-28.1%; P = 0.36), implantation (Group I: 17.5%; Group II: 16.7%; P = 0.90), clinical pregnancy (Group I: 28%; Group II: 24%; P = 1.0), miscarriage (Group I: 14.3%; Group II: 0; P = 0.33), ongoing pregnancy (Group I: 24%; Group II: 24%; P = 1.0), or live births (Group I: 24%, 6/25; Group II: 24%, 6/25; P = 1.0).Conclusions: The results indicate that the leukocytospermia may not have a negative effect on the outcomes of ICSI or IMSI cycles. Nevertheless, it seems that it is necessary to more precisely determine the effects, if any, of seminal leukocytes on fertilisation and implantation processes. Such efforts will help to establish a more reliable leukocyte threshold, which could eventually demonstrate whether there is a negative influence on the ART procedures.